2023
DOI: 10.3390/plants12040845
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein-Rich Extracts from Chondrus crispus as Biostimulant and in Enhancing Tolerance to Drought Stress in Tomato Plants

Abstract: The application of seaweed extract-based biostimulants is a promising approach for achieving sustainable agriculture, with an enormous potential of improving crop yield and mitigating climate change effects. Abiotic stressors, such as drought, are major factors resulting in tomato (Solanum lycopersicum L.) yield losses and seaweed-based biostimulants have been proposed as an eco-friendly strategy to counteract this negative impact. Chondrus crispus is a common red seaweed widely used as source of carrageenans,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
(81 reference statements)
2
5
0
Order By: Relevance
“…The results highlighted that Malvaceae-derived PH (PH1) was highly effective in enhancing plant recovery after all drought stress events while the positive effect of Fabaceae-derived PH (PH2) was detected only during the recovery period after the first stress event. The above findings are in line with a study of Domingo et al (2023) where foliar applications of a vegetal protein hydrolysate conferred drought resistance to tomato plants resulting in higher biomass and shoot height. Metabolomic results allowed to investigate the changes induced by the best performing PH treatment (PH1) on metabolic profile of leaves.…”
Section: Discussionsupporting
confidence: 89%
“…The results highlighted that Malvaceae-derived PH (PH1) was highly effective in enhancing plant recovery after all drought stress events while the positive effect of Fabaceae-derived PH (PH2) was detected only during the recovery period after the first stress event. The above findings are in line with a study of Domingo et al (2023) where foliar applications of a vegetal protein hydrolysate conferred drought resistance to tomato plants resulting in higher biomass and shoot height. Metabolomic results allowed to investigate the changes induced by the best performing PH treatment (PH1) on metabolic profile of leaves.…”
Section: Discussionsupporting
confidence: 89%
“…The high economic importance of tomato stimulated investigations of protein hydrolysate supply to enhance plant tolerance to salinity stress. Domingo et al [ 18 ] demonstrated the high prospects of Chondrus crispus extract hydrolysate as a remarkable source of protein, protecting tomato against salt stress. Francesca et al [ 19 ] reported the beneficial effect of Saccharomyces cerevisiae yeast autolysate on tomato plants under high salinity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to playing role in human health promotion, this genus has the potential to be utilized as a biostimulant in the horticultural and agricultural sectors. Recently, the protein-rich extract of C. crispus was first used as biostimulant to enhance the growth and drought tolerance of tomato plants [147].…”
Section: Discussionmentioning
confidence: 99%